Pengaruh Kualitas Pelayanan Puskesmas Terhadap Kepuasan Pasien BPJS Menggunakan Metode Service Quality - Erinda Cahya Herani; Ismi Mashabai (Jurnal Rekayasa Proses dan Industri Terapan, 2023)
Lopok Health Center is one of the government agency health centers. The problem that occurs at the Lopok Health Center is complaints from patients. This study aims to measure patient satisfaction with service quality, knowing the GAP value. The measurement of the quality of puskesmas services uses the service quality method with five dimensions, tangibles, reliability, responsiveness, assurance and empathy using a Likert scale. The results of service quality calculations obtained GAP values of tangibles dimensions (-0.6075), reliability (0.115), responsiveness (-0.08), assurance (-0.035), and empathy (-0.1825) which showed that the quality of puskesmas services given less in accordance with the expectations of the patient's wishes.